Evaluation of Blue Light Technology in Colonoscopy - Nichols, Emma Hitt (MD Conference Express, 2015)
Over the past several decades, blue light technology used in endoscopy (eg, colonoscopy) has evolved. The most recent advances include second-generation, high-definition narrow-band imaging and blue laser imaging. However, these technologies do not necessarily improve adenoma detection rates or miss rates, according to recent studies.